2009
DOI: 10.1055/s-0029-1234035
|View full text |Cite
|
Sign up to set email alerts
|

Malaria in Pregnant Woman Masquerading as HELLP Syndrome

Abstract: Malaria may be complicated by development of thrombocytopenia, elevated liver enzymes, and/or hemolysis, which may be difficult to distinguish from HELLP (hemolytic anemia; elevated liver enzymes; low platelet count) syndrome in a pregnant patient. A 33-year-old woman developed a HELLP-like syndrome and persistent fever postpartum without symptoms of preeclampsia. A malaria blood smear was performed and was positive for Plasmodium falciparum. The patient was immediately treated with quinine. The follow-up was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Acute fatty liver of pregnancy (AFLP) and hemolysis, elevated liver enzymes, and low platelet count (HELLP syndrome) are associated with significant maternal and fetal morbidity and mortality (43,44). In previous studies, pregnant women infected with P. falciparum were shown to develop hepatitis (45) or HELLP-like syndrome (46)(47)(48). The patients proceeded to spontaneous abortion, stillbirth, and premature delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Acute fatty liver of pregnancy (AFLP) and hemolysis, elevated liver enzymes, and low platelet count (HELLP syndrome) are associated with significant maternal and fetal morbidity and mortality (43,44). In previous studies, pregnant women infected with P. falciparum were shown to develop hepatitis (45) or HELLP-like syndrome (46)(47)(48). The patients proceeded to spontaneous abortion, stillbirth, and premature delivery.…”
Section: Discussionmentioning
confidence: 99%
“…It lives as a parasite in other organisms, namely man and mosquito. The plasmodium parasite is dependent on a single species of mosquito, anopheles, which is the only species capable of serving as the host of it (Ducarme, 2008…”
Section: Life Cycle Of Malaria Parasite In Nigeriamentioning
confidence: 99%
“…Knowledge is one of the important elements in any effort targeted towards the reduction of disease burden such as malaria (Minnesota Health Acrim Team, 2010) (Ducarme et al;2008) reported that the failure to establish the level of knowledge of community members regarding malaria appeared to be responsible for the mobility of intervention programmes to achieve suitable control. Consequently every women is expected to possess an appreciable level of knowledge of the cause, breeding sources, mode of transmission, consequences and prevention for successful eradicative of the disease in any given community.…”
Section: Introductionmentioning
confidence: 99%
“…At the travel destination, infectious diseases, such as malaria, Zika, and SARS-CoV-2, pose risks to pregnant people and their fetuses [2][3][4][5][6][7]. Pregnant people are more likely to attract mosquitoes that can cause malaria and Zika than their non-pregnant counterparts [8,9], and pregnant people have more severe malaria infections, as well as increased risk for developing pregnancy-specific complications, including preterm birth, low birth weight, congenital infection, miscarriage, stillbirth, and death [10][11][12][13][14][15][16][17]. Zika can cause fetal anomalies, including severe fetal brain injury, fetal growth restriction, miscarriages, and stillbirths, as well as ocular changes and hearing loss [7,[18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%